2021
DOI: 10.3390/insects12100901
|View full text |Cite
|
Sign up to set email alerts
|

Towards Integrated Pest and Pollinator Management in Intensive Pear Cultivation: A Case Study from Belgium

Abstract: Recently, the concept of Integrated Pest Management (IPM) was further extended into Integrated Pest and Pollinator Management (IPPM). Implementation of IPPM strategies entails the combination of actions for pest and pollinator management providing complementary or synergistic benefits for yield and/or quality of the harvest. The aim of this study was to examine IPPM elements (i.e., mixed hedgerow, nesting boxes for mason bees, Osmia spp.) and demonstrate their impact in the practical context of modern commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Innovative ways of applying pesticides in combination with D. suzukii baits or bait sprays [48], such as an attract-and-kill formulation [49,50], or using oviposition antagonist chemicals [51], phenology models to predict D. suzukii populations [52], and careful pesticide timing, could be helpful in minimizing insecticide use in various fruit crops. Developing an D. suzukii management plan under the newly evolving framework of integrated pest and pollinator management (IPPM) [53][54][55][56] by combining selective methods of applying pesticides, the selection of less-pollinator toxic pesticides, as well as the readjusting the spray timing, may reduce the potential risk of pesticide exposure to pollinator communities in farm landscape. A similar framework could also be developed for other non-target arthropod species (e.g., species that help in biological control such as parasitoids and predators) that are usually present in fruit farms, and could provide important ecosystem services by regulating pest populations [57].…”
Section: Resultsmentioning
confidence: 99%
“…Innovative ways of applying pesticides in combination with D. suzukii baits or bait sprays [48], such as an attract-and-kill formulation [49,50], or using oviposition antagonist chemicals [51], phenology models to predict D. suzukii populations [52], and careful pesticide timing, could be helpful in minimizing insecticide use in various fruit crops. Developing an D. suzukii management plan under the newly evolving framework of integrated pest and pollinator management (IPPM) [53][54][55][56] by combining selective methods of applying pesticides, the selection of less-pollinator toxic pesticides, as well as the readjusting the spray timing, may reduce the potential risk of pesticide exposure to pollinator communities in farm landscape. A similar framework could also be developed for other non-target arthropod species (e.g., species that help in biological control such as parasitoids and predators) that are usually present in fruit farms, and could provide important ecosystem services by regulating pest populations [57].…”
Section: Resultsmentioning
confidence: 99%
“…Predator energy use, however, did not differ between organic and IPM orchards, indicating that orchard management did not affect traits related to body size and metabolic rate. Besides local management, landscape is known to shape predator communities, with natural enemies benefitting from the presence and proximity of SNH structures such as mixed hedgerows and generally increasing with higher landscape complexity and heterogeneity (Beliën et al, 2021; Haan et al, 2019). This was confirmed by our study, which showed increased predator abundance and family richness with higher SNH cover and, in the case of abundance, also when SNH was closer to the orchards.…”
Section: Discussionmentioning
confidence: 99%
“…They help to control lepidopterans, storage pests, and infections [45]. Depending on the species and mode of application, pollinators can be exposed to various biopesticides by being used as entomovectors, through contact by foragers, ingestion, or from within or near their nests when applied for parasite control [30,131]. The concept of pollinators as entomovectors to distribute biopesticides [131] has been in use since the 1990s and involves using insects to disperse biological control agents to target plants; however, it was not until 2007 that it was officially acknowledged in the literature [30,131].…”
Section: Biopesticides In Agricultural Settingsmentioning
confidence: 99%